Petroleum and natural gas engineering-What is it? - Abd. Razak, Mohd. Razif (Faculty of Chemical & Natural Resources Engineering, 1987)
This article discusses on the process and operation that involve in petroleum and natural gas engineering that including locating the oil reservoir, drilling the exploration well, evaluating the formation, developing the field, producing the oil and transporting the oil.